Analysis of austenite-martensite phase boundary and twinned microstructure in shape memory alloys: The role of twinning disconnections. (1st February 2019) - Bronstein, Emil; Faran, Eilon; Shilo, Doron
Abstract: An austenite-martensite phase boundary in shape memory alloys (SMA) is associated with a periodic microstructure of martensite twin lamellas. Microscopy studies show that the period, which represents the thickness of the twin lamellas, increases with the distance from the habit plane. This observation is often overlooked when the microstructure and energy of the austenite-martensite interface are evaluated. In this paper we introduce a model that reproduces the variation in the twin lamella period. For this purpose, the overall energy of the phase boundary and the accompanied twinned microstructure is formulated and minimized. In particular, the effect of twinning disconnections, via which twins are tapered or broaden, and the additional energy due to the disconnections, are considered. Fittings of model predictions with measurements based on microscopy images provide evaluations of the twin boundary and twinning disconnection energies. Comparison of the results with expressions based on the theory of dislocations indicates that interactions between disconnections play a dominant role in determining the overall energy of twinning disconnections. Graphical abstract: Image 1